BAAL/CUP Seminar 2015: (De)Constructing Englishes: Exploring the implications of ontologies of the language for learning, teaching and assessment. (21st December 2016) - Hall, Christopher J
Abstract : This seminar was hosted by York St John University, UK, from 24–26 June 2015, and the co-ordinators were Chris Hall and Rachel Wicaksono (aided by Indu Meddegama, Clare Cunningham, Vicky Crawley, Ruth Ataçocuğu and Christian Sims). The seminar aimed to share diverse understandings of the ontological status of 'English' and to stimulate debate regarding the ways in which the language can be most effectively conceptualised for first language and second language learning, teaching and assessment. The seminar was organised around five sessions representing different frameworks. Following each session, an invited discussant highlighted major themes and led a general discussion. Individual papers are reported on below and the conclusion suggests their implications for applied linguistics.